Assessing Vitamin D Levels and Demographic Profiles of Adult Outdoor Patients: A Descriptive, Cross-sectional Study in a District Medical College Hospital of Bangladesh - Gani, ABM Shakil; Alam, Md Raqibul; Mahmood, Abdullah Al (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Vitamin D deficiency is a highly prevalent nutritional deficiency in Bangladesh. While the majority of the research has been done in the large metropolitan area, few studies have been conducted at the district level. Furthermore, little information has been discovered about the demographics of people with vitamin D deficiency. Thus, this study aimed to identify the district-level demographics of those who suffer from vitamin D insufficiency. Methods: A descriptive cross-sectional study was conducted among 197 participants attending medicine outdoors at Sheikh Hasina Medical College Hospital, Tangail, Bangladesh. Detailed interview on socio-demographic and lifestyle factors and anthropometric measurement was conducted. Serum vitamin D level was estimated by chemiluminescent immunoassay. Data were analyzed by SPSS 22.0. Results: About 46.2% of respondents had insufficient and 36.5% had deficient vitamin D levels. Serum vitamin D level was 22.68 ng/ml ± 7.83. Females (84.92%) had hypovitaminosis D more than males (78.87%) which was statistically significant. BMI, occupation, and monthly income had no significant role in different vitamin D status groups. Among females, wearing Burka had a significant relationship with low vitamin D levels. Conclusion: Females are more prone to suffer from low vitamin D levels especially those who had less sun exposure due to choice of clothing. Prophylactic supplements of vitamin D may be considered in this group. J Shaheed Suhrawardy Med Coll 2022; 14(1): 57-61